Optimizing Insulin Pump Therapy: A Quality Improvement Project. (November 2013) - Meade, Lisa T.; Rushton, Wanda E.
Purpose: The purpose of the study was to assess insulin pump use and provide ongoing education. Methods: A quality improvement project using a pump assessment questionnaire was implemented at an endocrinology office in the southeastern United States. The questionnaire was designed to evaluate all aspects of insulin pump therapy, including pump operations, infusion set failure, management of acute complications, and usage of advanced device features. Eighty-nine patients (80% with type 1 diabetes and 20% with type 2 diabetes) completed the questionnaire at the endocrinology practice. A certified diabetes educator reviewed the questions with each patient, identifying deficiencies and training opportunities. Results: The most common areas of deficiency identified after implementation of the assessment form included the following: expired or no basal insulin prescription in the event of pump failure or removal, no mupirocin (Bactroban®, GlaxoSmithKline, Research Triangle Park, North Carolina) prescription for suspected site infections, lack of insulin syringe if pump stopped working, failure to check urine ketones, no antiemetic prescription for sick day intervention, using manual bolus instead of bolus calculator, and lack of in-date glucagon kit. Conclusions: Use of a pump assessment questionnaire allows for focused discussion concerning patient behaviors related to pump operations, troubleshooting, and self-management. Incorporating use of a pump assessment questionnaire into routine practice may result in improved patient education and avoidance of adverse events specific to insulin pump therapy.